Effect of polychlorinated biphenyls (PCBs) and 1,1,1-trichloro-2,2,-bis (4-chlorophenyl)-ethane (DDT) in follicular fluid on the results of in vitro fertilization-embryo transfer (IVF-ET) programs - Jirsová, Simona; Masata, Jaromír; Jech, Libor; Zvárová, Jana (Fertility and sterility, 2010)
OBJECTIVE: To establish the effect of chlorinated organic compounds on fertility. DESIGN: We analyzed the influence of polychlorinated biphenyls (PCBs) and pesticides in follicular fluid on the number of fertilized oocytes, the quality of oocytes and embryos, pregnancy rate, and number of embryos cryoconserved in IVF-ET program. SETTING: Department of Gynecology and Obstetrics, Charles University, First Faculty of Medicine and General Teaching Hospital, Prague, Czech Republic. PATIENT(S): Patients from the Center of Assisted Reproduction. INTERVENTION(S): We collected the follicular fluid of 99 infertile women. MAIN OUTCOME MEASURE(S): The levels of xenobiotics in follicular fluid were examined by high-resolution mass spectrometry and gas chromatography. Correlations between the levels of xenobiotics and IVF-ET program results were statistically analyzed. RESULT(S): The PCB levels varied from 0.1 to 254.6 ng/g of fat. Levels of DDT and its metabolites varied from 0.3 to 35 228.8 ng/g of fat. A correlation was found between the number of diploid oocytes and the level of DDT, the fertilization of oocytes and level of PCB 158, and the pregnancy rate and the number of embryos cryoconserved and levels of PCB 47. CONCLUSION(S): Xenobiotics can be detected in the fat compartment of the follicular fluid. Some correlation to the IVF-ET program results was established, to a degree that might be considered of concern, although it was not statistically significant at the 5% level.
Keywords: xenobiotika; dospělí; DDT; Female; Follicular Fluid; Polychlorinated Biphenyls; Embryo Transfer; fertilizace in vitro; přenos embrya; Adult; výsledek terapie; ženské pohlaví; polychlorované bifenyly; Pregnancy Rate; lidé; Fertilization in Vitro; těhotenství; Treatment Outcome; ženská infertilita; prognóza; Xenobiotics; Infertility, Female; Environmental Pollutants; úhrn těhotenství na počet žen v reprodukčním věku; Pesticides; Prognosis; látky znečišťující životní prostředí; Pregnancy; folikulární tekutina; pesticidy; Humans